2021
DOI: 10.3390/app11052299
|View full text |Cite
|
Sign up to set email alerts
|

Belt Conveyors Rollers Diagnostics Based on Acoustic Signal Collected Using Autonomous Legged Inspection Robot

Abstract: Growing demand for raw materials forces mining companies to reach deeper deposits. Difficult environmental conditions, especially high temperature and the presence of toxic/explosives gases, as well as high seismic activity in deeply located areas, pose serious threats to humans. In such conditions, running an exploration strategy of machinery parks becomes a difficult challenge, especially from the point of view of technical facilities inspections performed by mining staff. Therefore, there is a growing need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…When applied in an unsupervised way, the approach can be used for predicting the remaining useful life in the absence of available run-to-failure data, as was done in [22] using the autoencoder based methodology to analyze the vibrations of a robotic arm. Skoczylas et al [23] used a diagnostic feature extracted from the spectral coefficients of the acoustic signal to identify the faulty operation of the rotating elements of the belt conveyor using the autocorrelation characteristics. Ho et al [24] suggested using Blind Source Separation as a signal decomposition approach to analyze vibration data of rotating bearings for the detection of fault patterns and signatures.…”
Section: Analysis Of Industrial Machinery Data For Predictive Maintenancementioning
confidence: 99%
“…When applied in an unsupervised way, the approach can be used for predicting the remaining useful life in the absence of available run-to-failure data, as was done in [22] using the autoencoder based methodology to analyze the vibrations of a robotic arm. Skoczylas et al [23] used a diagnostic feature extracted from the spectral coefficients of the acoustic signal to identify the faulty operation of the rotating elements of the belt conveyor using the autocorrelation characteristics. Ho et al [24] suggested using Blind Source Separation as a signal decomposition approach to analyze vibration data of rotating bearings for the detection of fault patterns and signatures.…”
Section: Analysis Of Industrial Machinery Data For Predictive Maintenancementioning
confidence: 99%
“…This work is a part of the THING (subTerranean Haptic INvestiGator) project, which involves using a modified commercial robot to take over the necessary monitoring processes currently performed by humans [34][35][36]. The inspection procedure, with the use of this apparatus together with the description of other algorithms (damage detection based on acoustics and thermovision), has been presented in the previous works [37,38].…”
Section: Autonomous Inspection Robot and Inspection Proceduresmentioning
confidence: 99%
“…which involves using a modified commercial robot to take over the necessary monitoring processes currently performed by humans [34][35][36]. The inspection procedure, with the use of this apparatus together with the description of other algorithms (damage detection based on acoustics and thermovision), has been presented in the previous works [37,38]. For the purposes of the inspection, the robot walked around the conveyor route and recorded a video.…”
Section: Autonomous Inspection Robot and Inspection Proceduresmentioning
confidence: 99%
“…There are plenty of articles focused on the diagnostics of drive units (gearboxes, pulleys) using vibration analysis or infrared thermography [2][3][4][5][6] or temperature [7]. The conveyor belt has been defined as one of the most expensive component in conveyor, thus various NDT techniques (image analysis, laser scanning, magnetic field measurement) have been applied [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%